Minimalisme dan zuhud: Perbandingan gaya hidup barat dan islam serta manfaatnya bagi kesehatan mental - Rizky Susanti; Ahmad Sulaiman (Cognicia, 2022)
Materialist lifestyle produces consumptive behavior which ultimately has a broad impact on a person. The most dangerous impact is on mental health where individuals are more susceptible to depression when they do not feel they have enough. Responding to this condition, modern western society has created minimalist lifestyle. This lifestyle is characterized by a deliberate restriction of ownership of things. As for Islam, there is the concept of zuhud which means turning a Muslim away from all worldly things. Although by naked eye, minimalist behavior has similarities with zuhud, there are fundamental differences between the two. The purpose of this study was to identify the differences between minimalism and zuhud and their effect on mental health. Using the literature review method, this study reveals that zuhud guarantees a more stable and authentic mental health, especially for Muslims. The greater positive influence is caused by the reference point of the performer of zuhud in the hereafter rather than the world, and zuhud having an integrative-interconnective relationship with other rites in Islam.   Keywords: islamic psychology, mental health, minimalism, zuhud